2019
DOI: 10.5194/acp-19-12261-2019
|View full text |Cite
|
Sign up to set email alerts
|

NH<sub>3</sub> emissions from large point sources derived from CrIS and IASI satellite observations

Abstract: Abstract. Ammonia (NH3) is an essential reactive nitrogen species in the biosphere and through its use in agriculture in the form of fertilizer (important for sustaining humankind). The current emission levels, however, are up to 4 times higher than in the previous century and continue to grow with uncertain consequences to human health and the environment. While NH3 at its current levels is a hazard to environmental and human health, the atmospheric budget is still highly uncertain, which is a product of an o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

5
4

Authors

Journals

citations
Cited by 108 publications
(96 citation statements)
references
References 92 publications
1
79
0
Order By: Relevance
“…Similarly, the diurnal emission profile can be approximated by using the diurnal emission profile for livestock that is used to prepare emissions for the GEM-MACH model. Most of the emissions around Lethbridge are from livestock, which has a peak in the morning to middle of the day following cattle activity including feeding and excretion and the in-creasing surface temperatures (Denmead et al, 2014;Van Haarlem et al, 2008), and are thus emitted before the satellite overpass time (∼ 01:30 LT). Thus, the inventory value from an hour before the overpass (12:30 LT) is used to adjust the emissions to daily averages by a factor of 1/1.44 leading to a final annual emission total of 37.1 ± 6.3 kt yr −1 .…”
Section: Emission Estimate For a Concentrated Agricultural Regionmentioning
confidence: 99%
“…Similarly, the diurnal emission profile can be approximated by using the diurnal emission profile for livestock that is used to prepare emissions for the GEM-MACH model. Most of the emissions around Lethbridge are from livestock, which has a peak in the morning to middle of the day following cattle activity including feeding and excretion and the in-creasing surface temperatures (Denmead et al, 2014;Van Haarlem et al, 2008), and are thus emitted before the satellite overpass time (∼ 01:30 LT). Thus, the inventory value from an hour before the overpass (12:30 LT) is used to adjust the emissions to daily averages by a factor of 1/1.44 leading to a final annual emission total of 37.1 ± 6.3 kt yr −1 .…”
Section: Emission Estimate For a Concentrated Agricultural Regionmentioning
confidence: 99%
“…Due to the nature of wildfires with plume heights reaching several kilometres, aerosol plumes produced by wildfires can be transported over vast distances (e.g. Damoah et al, 2004;Derwent et al, 2004;Duck et al, 2007;Lutsch et al, 2016Lutsch et al, , 2019. Plumes from larger fires can thus cause aviation hazards and affect regional air quality thousands of kilometres away from the source and even across continents (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric NH 3 is rapidly removed by wet and dry deposition as well as by reactions with acids in the atmosphere, and thus has a relatively short lifetime ranging from a few hours to a few days (Galloway et al, 2003;Dammers et al, 2019). NH 3 lifetime may be longer for certain cases, such as biomass burning emissions that inject NH 3 into the free troposphere, attenuating depositional and chemical losses, although physical and chemical mechanisms that lead to transport of NH 3 in biomass burning plumes over long distances remain uncertain (Lutsch et al, 2016(Lutsch et al, , 2019b.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Hu et al (2014) investigating NH 3 in downtown Toronto has shown that greenery within the city is an important source of NH 3 when temperatures are above freezing, and that potential sources at temperatures below freezing have yet to be investigated. Additionally, recent studies have shown the increased capacity for satellite-based instruments to measure spatial and temporal distributions of NH 3 total columns at global Warner et al, 2016;Shephard et al, 2020), regional Warner et al, 2017;Viatte et al, 2020), and point-source scales (Van Damme et al, 2018;Clarisse et al, 2019a;Dammers et al, 2019).…”
Section: Introductionmentioning
confidence: 99%